Developing an Assessment of Contraceptive Preferences in Botswana: Piloting a Novel Approach Using Best-Worst Scaling of Attributes - Gertz, Alida M.; Soffi, Ahmad Syahir Mohd; Mompe, Atlang; Sickboy, Ontiretse; Gaines, Averi N.; Ryan, Rebecca; Mussa, Aamirah; Bawn, Caitlin; Gallop, Robert; Morroni, Chelsea; Crits-Christoph, Paul (Frontiers in Global Women's Health, 2022)
Introduction To develop an attribute-based method for assessing patient contraceptive preferences in Botswana and pilot its use to explore the relationship between patient contraceptive preferences and the contraceptive methods provided or recommended to patients by clinicians. Methods A list of contraceptive attributes was developed with input from patients, clinicians, and other stakeholders. We assessed patient preferences for attributes of contraceptives using a discrete choice “best-worst scaling” approach and a multi-attribute decision-making method that linked patient attribute preferences to actual contraceptive method characteristics. Attribute-based patient method preferences and clinician recommendations were compared in 100 women seeking contraceptive services, and 19 clinicians who provided their care. For 41 of the patients, the short-term reliability of their preference scores was also examined. Results For 57 patients who wanted more children in the future, the degree of concordance between patients and clinicians was 7% when comparing the top attribute-based contraceptive preference for each woman with the clinician-provided/recommended method. When the top two model-based preferred contraceptive methods were considered, concordance was 28%. For 43 women who did not want more children, concordance was 0% when using the patient's model-based “most-preferred” method, and 14% when considering the top two methods. Assessment of the short-term reliability of preference scores yielded an intraclass correlation coefficient of 0.93. Conclusions A best-worst scaling assessment of attributes of contraceptives was designed and piloted in Botswana as a Contraceptive Preference Assessment Tool. The preference assessment was found to have high short-term reliability, which supports its potential use as a measurement tool. There was very low concordance between women's attribute-based contraceptive preferences and their clinician's provision/recommendations of contraceptive methods. Using such a preference assessment tool could encourage greater patient involvement and more tailored discussion in contraceptive consultations.